MANAJEMEN GEREJA DALAM PELAYANAN SEKOLAH MINGGU : Upaya Membangun Kesetiaan Anak terhadap Pelayanan Gereja - Yunardi Kristian Zega (Sekolah Tinggi Teologi Baptis Medan, 2021)
Sunday school is one of the supporting facilities in spiritual development for children, so they can get to know God the Creator from an early age. In addition, Sunday School can also be a forum for the church to lay the foundation of Christian faith for children, so that they can reflect the character of life in accordance with Bible teachings. However, what is happening today is that more and more Christian children are starting to leave the church. This was disclosed by Prof. Dr. Thomas Pentury, M.Sc., based on research results, there are as many as 50% of the Christian millennial generation in Indonesia who have left the church. Here it can be seen that the church today needs good management, especially in Sunday School activities so that the children who are being taught in the future remain faithful to serve in the church. Therefore, in this article the writer uses literature review to answer the problems raised. With the aim, that the church can have a picture or concept of good management in the Sunday School ministry, so that the children who are taught continue to have loyalty to church services.